2017
DOI: 10.1002/slct.201700042
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical Properties, Biological and Environmental Impact of Nb-saponites Catalysts for the Oxidative Degradation of Chemical Warfare Agents

Abstract: Niobium‐containing saponite clays are active catalysts, under mild ambient conditions and in the presence of aqueous hydrogen peroxide, in the oxidative abatement of sulfur‐containing blister chemical warfare agent simulants, such as (2‐chloroethyl)ethyl sulfide. Over a Nb‐saponite solid, a complete, selective and safe abatement of the chemical agent was attained within 8 h. The biological and environmental impact of the Nb‐containing nanostructured clays used as decontamination solids was assessed by specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
1
13
0
2
Order By: Relevance
“…The introduction of both Gd 3+ and Eu 3+ ions in the saponite framework affected the size of lamellae, that is comparable to what was observed for Nb 5+ and V 3+ -containing saponites prepared with the same synthetic procedure. 22 24 Similar results in terms of morphology and particle size were also observed for the reference monofunctionalized solids ( Figure S2 ).…”
Section: Resultssupporting
confidence: 81%
“…The introduction of both Gd 3+ and Eu 3+ ions in the saponite framework affected the size of lamellae, that is comparable to what was observed for Nb 5+ and V 3+ -containing saponites prepared with the same synthetic procedure. 22 24 Similar results in terms of morphology and particle size were also observed for the reference monofunctionalized solids ( Figure S2 ).…”
Section: Resultssupporting
confidence: 81%
“…These disadvantages could be overcome by design synthetic strategies based on the direct insertion of the lanthanide ions in the clay synthesis gel, as previously performed with vanadium and niobium metals. 5,31,32 Based on these considerations, in this study, two luminescent lanthanides, Tb 3+ and Eu 3+ , were simultaneously incorporated in the structure of a synthetic saponite clay (hereaer named Na-TbEuSAP), using a single-step hydrothermal approach. A solid with only Tb 3+ ions was also prepared as a reference (hereaer named Na-TbSAP).…”
mentioning
confidence: 99%
“…In detail, Na-TbEuSAP and Na-TbSAP samples were prepared by a modied one-pot hydrothermal synthesis protocol, followed by sodium-exchange process (Scheme S1 in the ESI †). 5,31,32 Eu 3+ and Tb 3+ were introduced in the form of chloride salts during the synthesis gel along with the silicon, aluminium and magnesium precursors. The nal materials were then submitted to ionic exchange procedure to replace the different cations located in the saponite gallery (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that these strains were highly sensitive to toxic factors of various natures [ 49 ]. The biotoxicity of PB samples was evaluated on both acute and chronic effects [ 49 , 50 ] at 25 °C and a concentration of solid phase ranged from 0.05 to 0.5 mg/mL.…”
Section: Methodsmentioning
confidence: 99%